Growth of big-leaf mahogany (Swietenia macrophylla) in natural forests in Belize - Shono, K.; Snook, Laura K. (2006)
The annual diameter measurements four years of 75 big-leaf mahogany (Swietenia macrophylla King) trees in natural forests in northwestern Belize were analyzed to determine growth rates. Mean diameter increment exceeded 1 cm year-1, with slightly higher growth rates in trees > 50 cm dbh. Inter-individual variation in growth rates was significant, with the fastest-growing individuals growing at rates greater than 2 cm year-1. Inter-annual variation in growth rates was also significant. The diameter growth of 1.21 ± 0.1 cm during a wetter year (1456 mm ppt) exceeded by 75% diameter growth of 0.69 ± 0.1 cm during a drier year (1181 mm ppt). The study revealed that mahogany trees as small as 23 cm dbh that were left standing after harvests could be expected to attain the commercial diameter of 60 cm during the 40 years between cutting cycles.